The photo-electrical properties of the p-Si/Fe(II)-polymeric complex/Au diode - Gündüz, Bayram; Turan, Nevin; Kaya, E.; Çolak, N. (My University, 2013)
In this study, the Schiff base monomer was prepared by a common condensation method of salicylaldehyde and (E)-3-amino-4-((3-bromophenyl) diazenyl)-1H-pyrazol-5-ol. The poly(Schiff base) was synthesized from the oxidative polycondensation of the Schiff base monomer with NaOCl in an aqueous alkaline medium. After obtaining Schiff base polymer, Fe(II)-polymeric complex with Fe(II) of Schiff base polymer was successfully synthesized. Ligand, monomer, Schiff base polymer and Fe(II)-polymeric complex were characterized using elemental analysis, 1H NMR, 13C NMR, FT IR, GPC, UV-vis and magnetic susceptibility. Then, we fabricated the p-Si/Fe(II)- polymeric complex/Au diode and investigated the electronic and photoconductivity properties of the p-Si/Fe(II)-polymeric complex/Au diode by current-voltage measurements under dark and various illumination conditions. We calculated the electrical and photo-electrical parameters of the p-Si/Fe(II)-polymeric complex/Au diode such as the rectification ratio (r), ideality factor (n), barrier height (?b), Richardson constant (A*), series (Rs) and shunt resistance (Rsh) and photocurrent (Iph), responsivity (R) and photoconductivity sensitivity (S). The obtained n values confirm the presence of a combination of recombination and diffusion currents in the p-Si/Fe(II)-polymeric complex/Au diode. The r, n, ?b, Rs and Rsh values of the p-Si/Fe(II)-polymeric complex/Au diode decreased with increasing illumination intensity. The Iph, R and S values of the p-Si/Fe(II)-polymeric complex/Au diode increased with increasing illumination intensity. The synthesized Fe(II)-polymeric complex exhibits semiconductor property, it can be used in production of the metal-semiconductor (Schottky) diode and it is sensitive to light. The p-Si/Fe(II)-polymeric complex/Au diode exhibits a photoconductivity effect. © 2013 Elsevier B.V.
Keywords: Fe (II)-polymeric complex; Illumination intensity; Photo-electrical parameters; Photoconductivity sensitivity; Schiff base polymer complexes